Pengaruh Variasi Pembebanan Terhadap Performansi Mesin Diesel Single-Fuel Berbahan Bakar Dexlite dan Liquified Petroleum Gas - Rahmandhika, Andinusa (Jurnal Mesin Nusantara, 2024)
Liquified Petroleum Gas (LPG) is an environmentally friendly alternative fuel, it would be a shame if it were not utilized. By making modifications to the diesel engine, it turns out that LPG can be used as a substitute for fuel oil. This research aims to determine the performance of a single-fuel diesel engine using Dexlite and 3 kg LPG. The method in this research is experimental research. Data was taken three times in each experiment with different load variations, then processed to obtain values for engine speed, torque, power, SFC and thermal efficiency. The research results show that the maximum torque value for dexlite and LPG is 22.4375 N.m. The maximum power value for dexlite and LPG is 3.9924 kW. The minimum SFC value for dexlite is 1.3089 kg/kW.hour while LPG is 0.9481 kg/kW.hour. The maximum thermal efficiency value for dexlite is 64.03% while for LPG it is 80.8%. The results of this research show that the torque and power values for each fuel have the same value, this is because the engine speed and load are the same. However, the SFC value and thermal efficiency of each fuel have different values, where the SFC value of 3 kg LPG is lower than Dexlite and the thermal efficiency value of 3 kg LPG is higher than Dexlite.